Spiritual Integration in Financial Frameworks: Its Relationship to Long-Term Financial Planning and Subjective Well-Being Among Generation Z in South Sulawesi - Sri Wahyuni; Husmaruddin Husmaruddin; Goso Goso (Universitas Proklamasi 45, 2026)
Generation Z in South Sulawesi faces challenges in managing their finances carefully amid a consumerist lifestyle and modernization pressures. This study examines the influence of spiritual integration on long-term financial planning and subjective well-being. A quantitative approach is used, employing the survey method. The carefully prepared questionnaire was administered to 100 respondents from Generation Z, aged 15 to 29, all from South Sulawesi. These respondents were selected using the purposive sampling method. The collected data were then analyzed using the Partial Least Squares Structural Equation Modeling technique, or PLS-SEM for short. The results of the analysis show that spirituality plays a major role in fostering a more responsible financial attitude, improving long-term financial planning, and strengthening people's subjective well-being. In addition, long-term financial planning partially mediates the relationship between spiritual integration and subjective well-being. These findings confirm that a financial approach that incorporates spiritual values can be an effective strategy to improve the quality of life among young people. They highlight the importance of integrating the spiritual dimension into financial education programs.